Nilai-Nilai Pendidikan Multikultural dalam Perspektif Pemikiran Nurcholish Madjid - Nurjannah Nasution; Erawadi Erawadi; Anhar Anhar (Studi Multidisipliner: Jurnal Kajian Keislaman, 2020)
AbstractThis study aims to reveal the meaning and values of multicultural education in the perspective of Nurcholish Madjid's thinking by using the research method of character studies. The results of this study can be concluded that Nurcholish Madjid that in referring to the multicultural term Nurcholish Madjid uses the term plurality more. Plurality is a plural or plural society which is the design and sunnatulah Allah Almighty for mankind because there is no single and equal society in all aspects. The multicultural education values found, namely the value of democracy (must be absolutivism / free to express opinions and accept criticism), the value of justice (must be fair and be a referee / mediator in upholding something), the value of equality (all human beings are the same that distinguishes only the level devotion), human values (humans are not justified to denigrate one another) and tolerance values (mutual respect and respect for other religions and give freedom of worship).Keywords: Education; Multicultural; Nurcholish Madjid. AbstrakPenelitian ini bertujuan untuk mengungkapkan makna dan nilai-nilai pendidikan multikultural dalam perspektif pemikiran Nurcholish Madjid dengan menggunakan metode penelitian studi tokoh. Hasil penelitian menunjukkan bahwa Nurcholish Madjid dalam menyebut istilah multikultural lebih banyak menggunakan istilah pluralitas. Pluralitas adalah suatu masyarakat majemuk atau plural yang merupakan design dan sunnatulah Allah swt untuk umat manusia karena tidak ada masyarakat yang tunggal dan sama dalam semua segi. Adapun nilai-nilai pendidikan multikultural yang didapati, yaitu nilai demokrasi (harus absolutivisme/ bebas mengutarakan pendapat dan menerima kritikan), nilai keadilan (harus bersikap adil dan menjadi wasit/penengah dalam menegakkan sesuatu), nilai kesetaraan (semua manusia sama yang membedakannya hanya tingkat ketaqwaan), nilai kemanusiaan (manusia tidak dibenarkan untuk merendahkan satu sama lain) dan nilai toleransi (saling menghormati dan menghargai agama lain serta memberi kebebasan beribadah). Kata Kunci: Pendidikan; Multikultural; Nurcholish Madjid.